Effect of gamma-ray irradiation on the device process-induced defects in 4H-SiC epilayers. (November 2016) - Miyazaki, T.; Makino, T.; Takeyama, A.; Onoda, S.; Ohshima, T.; Tanaka, Y.; Kandori, M.; Yoshie, T.; Hijikata, Y.
Abstract: We investigated the gamma-ray irradiation effect on 4H-SiC device process-induced defects by photoluminescence (PL) imaging and deep level transient spectroscopy (DLTS). We found that basal plane dislocations (BPDs) that were present before the irradiation were eliminated by gamma-ray irradiation of 1 MGy. The reduction mechanism of BPD was discussed in terms of BPD-threading edge dislocation (TED) transformation and shrinkage of stacking faults. In addition, the entire PL image was gradually darkened with increasing absorbed dose, which is presumably due to the point defects generated by gamma-ray irradiation. We obtained DLTS peaks that could be assigned to complex defects, termed RD series, and found that the peaks increased with absorbed dose.